Chile : Technical Assistance Report-Central Bank Services to Non-bank Financial Institutions. (IMF Staff Country Reports; Country Report ;, 2020)
This Technical Assistance report on Chile constitute technical advice provided by the staff of the IMF to the Banco Central de Chile (BCCh) in response to their request for technical assistance. The BCCh is considering broadening access to its services beyond commercial banks and some Financial Market Infrastructures. The mission emphasized the overarching requirement for all central bank counterparts to be adequately regulated and supervised, to mitigate the central bank's operational, financial, and reputational risks. Recent changes to the banking law facilitate consolidation of the banking supervisor into the nonbank supervisor. This move should facilitate equal treatment across participants and reduce the prospect of regulatory arbitrage. The new architecture should ease, though not eliminate, coordination efforts between BCCh and authorities when it comes to maintaining financial stability. By applying the assessment framework to Chile, the mission recommended some minor broadening of Nonbank Financial Institutions access to BCCh services, while noting that it should have the power to provide liquidity to any nonbank financial sector to contain spillovers that may otherwise threaten financial stability more generally.